Pre-stress Modal Analysis of Space Frame Chassis Structure Using Finite Element Method - A.B. Marzuki, M.; F.M. Azmi, M.; R.N. Mohamed, A.; A.A. Bakar, M.; A.M. Nawi, M. (International Journal of Engineering and Technology, 2018)
Modal analysis is a method to investigate the dynamic characteristic of a structure in the form of resonance frequencies, mode shapes and natural frequencies. A number of methods can be adopted to study the dynamic response of a structure, which include experimental modal analysis, operational modal analysis and operational deflection shapes. The modal analysis can be studied through experimentation, but with the advancement in computational field, dynamic characteristic of a structure is often analysed through finite element software package. The main objective of the modal analysis in this paper is to investigate the effect of pre-stressed space frame chassis using the finite element software â€“ ANSYS APDL. ANSYS APDL is utilised to generate the chassis model, defining the material properties, element type and size, boundary condition and model constraint. The model is solved and plotted using the appropriate result plot in ANSYS APDL. The load factor We/Wd is used to study the effect of different load distribution on the mode shape frequencies. The result shows that there are minimal effects of pre-stressed in comparison with unloaded structure. However, the first mode shape recorded the highest change in mode frequency in respect with increasing load factor. The significance of this study is diverse; in particular, it provides the foundation in determining pre-stressed effect on space frame chassis structure.Â Â